The relationship between obstructive sleep apnea and atrial remodeling, fibrosis and inflammation - Dasheng Lu; Kai Wang (PLoS ONE, 2025)
Background Obstructive sleep apnea (OSA), characterized by chronic intermittent hypoxia (CIH) is associated with atrial fibrillation. We explored the effects of OSA on atrial remodeling, fibrosis and inflammation, using both clinical and experimental studies. Methods A total of 105 patients were grouped into control (n = 52), mild to moderate OSA (m-OSA, n = 27), and severe OSA (s-OSA, n = 26) groups. The participants underwent echocardiography and blood tests for interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), collagen type 1 (col-1), and collagen type 3 (col-3). In order to eliminate the interference of obesity, an experimental study was performed using lean mice exposed to CIH. Results In clinical patients, severe OSA featured higher body mass index (BMI) than control (28.12 ± 3.43 versus 24.40 ± 3.56 kg/m2, p < 0.001). Left atrial diameter was significantly higher in s-OSA group than in control group (38.35 ± 4.89 versus 35.39 ± 5.29 mm, P = 0.012). Patients with OSA had higher TNF-α levels than those in the control (P = 0.007). Consistently, plasma IL-1β levels were significantly elevated in the s-OSA and m-OSA groups compared with those in the control group. However, we did not observe significant changes in plasma col-1 and col-3 in patients with OSA. Subgroup analysis of patients with a BMI less than 25 kg/m2 showed that the inflammatory cytokine TNFα is correlated with OSA, rather than with BMI. In animal experiments, using lean mice exposed to IH for 3 weeks, WGA and Masson’s staining showed that IH enlarged the atrial myocardium and promoted atrial fibrosis. Atrial mRNA expression of TGFβ、col-1, col-3, IL-6, and TNF-α was significantly elevated after IH exposure. Conclusion OSA, characterized by CIH, was associated with the increased atrial structural remodeling, fibrosis and inflammation.